2019
DOI: 10.1002/jsfa.10121
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative risk assessment of phthalates in edible vegetable oil consumed by Chinese residents

Abstract: BACKGROUND: Phthalates have been widely used as plasticizers in various industries and are widely focused on in the international community as a result of their reproductive toxicity. Exposure of Chinese residents to phthalates via edible vegetable oil occurs often. In the present study, gas chromatography-mass spectrometry was used to detect the two main phthalates bis(2-ethylhexyl) phthalate (DEHP) and dibutyl phthalate (DBP) in four major edible vegetable oil sources: an edible oil blend, soybean oil, peanu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The phthalate with the highest detection rate was DBP (13.48%), followed by DEHP (7.78%). Nevertheless, the two phthalates had the lowest detection rates in soybean oil, which were 1.94% (DEHP) and 5.16% (DBP) [ 229 ].…”
Section: Occurrence Of Paes In Foodmentioning
confidence: 99%
“…The phthalate with the highest detection rate was DBP (13.48%), followed by DEHP (7.78%). Nevertheless, the two phthalates had the lowest detection rates in soybean oil, which were 1.94% (DEHP) and 5.16% (DBP) [ 229 ].…”
Section: Occurrence Of Paes In Foodmentioning
confidence: 99%
“…Table 2 summarizes the extraction techniques adopted in the last three years to analyze PAEs in environmental and food matrices. It is possible to observe that the most common extraction techniques used to extract phthalates from environmental and food samples are LLE [ 62 , 63 , 64 , 71 , 74 , 76 , 77 , 89 , 91 , 94 , 95 , 96 , 99 , 104 , 106 , 109 , 110 , 112 ], SPME [ 60 , 69 , 81 , 82 , 92 , 93 , 115 ], QuEChERS-dSPE [ 79 , 88 , 102 ], SPE [ 68 , 75 ], and soxhlet [ 100 , 101 , 114 ].…”
Section: Analytical Approachesmentioning
confidence: 99%
“…[1,2] Therefore, PAEs can be detected in air, [3,4] soil, [5,6] drinking water [7,8] and food products. [9,10] Various studies showed that PAEs exhibit toxic effects on the reproductive system, neuroendocrine system, and immune system. [11][12][13][14] Therefore, intensive research efforts are dedicated to the efficient degradation of these persistent organic pollutants in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…From these products, PAEs constantly leach out into the environment [1,2] . Therefore, PAEs can be detected in air, [3,4] soil, [5,6] drinking water [7,8] and food products [9,10] . Various studies showed that PAEs exhibit toxic effects on the reproductive system, neuroendocrine system, and immune system [11–14] .…”
Section: Introductionmentioning
confidence: 99%